Effect of Copper (II) Chloride Concentration towards Copper Ions Sorption on Natural Zeolite from Wonosari - Irnawati, Dyah; Widjijono, Widjijono; Wijaya, Karna; Asmara, Widya (The Indonesian Journal of Dental Research)
Copper-containing zeolite has been developed as an antibacterial material. It is obtained by reacting zeolite and salt solution with varied concentration of copper. Natural zeolite is abundant in Wonosari, Yogyakarta. The aim of this research was to investigate the concentration effect of copper (II) chloride solutions towards copper ions sorption on natural zeolite from Wonosari. Copper (II) chloride dihydrate powders, CuCl2. 2H2O, (Merck, Germany) and natural zeolite (Wonosari, Indonesia) were used. Zeolite powder (100 mesh) was washed and dried (200oC/2 hours). Copper (II) chloride solution with different concentrations (0.05 M, 0.10 M, 0.15 M, 0.20 M, and 0.25 M) were prepared. Zeolite and CuCl2 solutions (50 g/250 ml) were reacted at 60oC for 1 hour (n=5). The solutions were filtered, washed, and dried (100oC/24 hours). Copper ions amount were measured by XRF (Canberra Inc., USA). The data were analyzed by one way Anova. Mean values (% weight) of copper ions amount were 0.441 ± 0.029 % (0.05 M group), 0.588 ± 0.027 % (0.10 M group), 0.657 ± 0.014 % (0.15 M group), 0.676 ± 0.037 % (0.20 M group), and 0.737 ± 0.039 % (0.25 M group). The Anova showed that CuCl2 concentration influenced copper ions amount significantly (p<0.01). The differences among the groups were significant, except between 0.15 M and 0.20 M groups (p>0.05). Copper (II) chloride concentration influenced the copper ions sorption on natural zeolite from Wonosari. The 0.25M CuCl2 solution gave the highest copper ions amount.